Sulalatus Salatin and Tun Perak's Charisma in the Practice of the Laws of Nusantara Multiethnic Society - Harun, Jelani (Malay Literature, 2016)
In the 15th century, Malacca emerged as a city that became the focus of traders and travellers from all corners of the Nusantara. At that time, the states under the protection of Malacca and anyone who came to Malacca were subject to the laws of the Malacca Sultanate. This has been referred to many times by the author of Sulalatus Salatin , in the narration of events involving Malacca's relations with other states in the Nusantara world, and at the same time highlighting the practice of laws which took place in the multiethnic society residing in Malacca. Harshness is the general characteristic in the implementation of laws and this view is supported by works on Malay governance such as Taj -Salatin, Bustan al- Salatin and Thamarat -Muhimmah . However, harshness not accompanied by fairness and wisdom can lead to cruelty. This issue became part of the focus of Sulalatus Salatin's author's thinking while describing several myths, conflicts and philosophies of justice of the Malay rulers in Singapore and Malacca which is closely linked to attitude, leadership and knowledge of the rulers and leaders. This article will reevaluate the issue by drawing attention to the charisma of Tun Perak in the implementation of laws of the Malay sultanate, either towards the multiethnic society in the Nusantara or in the context of those residing in Malacca, in which the issues of harshness of laws are entangled, counterbalanced and intertwined with many incidents of slander, sedition and corruption that could destroy the history of Malay culture. Keywords: Tun Perak, laws, governance, historiography, philosophy, slander, corruption